Imam Ismail bin Al-Qasim and his manuscript (Mas'alat Talaq Aldawr): study and investigation - Al-Lahji, Jamil Ghaleb Ahmed (Journal of Islamic Sciences, 2023)
This research aims to identify the manuscript of Imam Ismail bin Al-Qasim on (Mas'alat Talaq Aldawr) As well as identifying the sayings of scholars on the issue of role divorce, as well as identifying the personal aspects of the imam who relies on God, Ismail bin Al-Qasim , and the descriptive, analytical and inductive approach was used , using the content analysis method. Bin Al-Qasim Invalid, and it is not permissible for the ignorant to learn it, nor for the scholars to issue fatwas about it because of its invalidity , according to the evidence from the Book and the Sunnah, and the scholars made clear in their statements the invalidity of the role divorce according to the Book and the Sunnah, and the era of Imam Al-Mutawakkil was distinguished by justice and equality, and interest in science and scholars, and there were scholarly migrations in all regions of Yemen, and it was One of the diligent imams, as he authored many books on the religious and moral side.
Keywords: manuscript; Imam Ismail bin Al-Qasim; divorce; marriage